Cloning and Functional Identification of SlPG49 in Solanum lycopersicum - Weiqiang Li; Liai Xu; Rui Xia; Ying Shen; Zhujun Zhu; Youjian Yu; Yunxiang Zang (Applied Sciences, 2021)
The modification and degradation of pectin in cell walls are necessary for the fruit softening process, which involves a series of pectin-modifying enzymes. Polygalacturonases (PGs) are a major group of pectin-hydrolyzing enzymes, which participate in fruit maturation, organ shedding, pollen development, and other processes by catalyzing the degradation of polygalacturonic acid. However, their function in plants has not yet been fully elucidated. In this paper, a full-length cDNA encoding SlPG49 was cloned from a tomato. Sequence alignment and phylogenetic analysis demonstrated that SlPG49 contains four typical conserved domains and belongs to clade E in PG classification. Quantitative real-time PCR analysis showed that SlPG49 was highly expressed in fruits during the softening stage, indicating that SlPG49 may be involved in fruit softening. Subcellular localization results revealed that SlPG49 was located in the cell membrane and the cell wall. In addition, an in vitro enzymatic activity assay confirmed that SlPG49 does have the ability to catalyze the hydrolysis of polygalacturonic acid. These results indicate that SlPG49 is a newly discovered PG gene involved in tomato fruit softening, and provide an experimental basis for elucidating the biological functions of plant PGs during fruit softening.